The relationship between the US state alcohol policy environment and individuals’ experience of secondhand effects: alcohol harms due to others’ drinking - Greenfield, Thomas K. (Alcohol Clin Exp Res, 2019)
INTRODUCTION: Although restrictive state alcohol policy environments are protective for individuals’ binge drinking, research is sparse on the effect of alcohol policies on alcohol’s harms to others (AHTO). We examined the lagged associations between efficacy of US state alcohol policies and number of harms from others’ drinking one year later. METHODS: Individuals with AHTO data in a nationally-representative sample of US adults (analytic sample n= 26,744) that pooled the 2000, 2005, 2010, 2015 National Alcohol Surveys and a 2015 National Alcohol’s Harm to Others Survey were linked with prior-year state-policy measures. We used two measures from the Alcohol Policy Scale (APS)—effectiveness in reducing a) binge drinking and b) impaired driving, based on experts’ efficacy judgments regarding 29 state alcohol policies. Three 12-month AHTO measures (due to another drinker) were experiencing: a) either family/marriage difficulties or financial troubles; b) being assaulted or vandalized; c) passenger with drunk driver or traffic accident. Multi-level models accounting for clustering within states and stratified by age groups (< 40 vs ≥ 40) examined associations between the APS and AHTO measures, controlling for individual covariates (gender, race, education, employment and marital status, family problem-drinking history) of the victim. RESULTS: Only for those aged < 40, the lagged APS-binge drinking and APS-impaired driving scores were each inversely associated with aggression-related harms and, separately, with drunk driving-related harm from someone else’s drinking (ps <. 05 to < .01). Family/financial harms were not associated with APS scores for either age group. Composite AHTO measures (any of 3 harm-types) also were inversely associated with stronger state alcohol policy environments (ps <. 05 to < .01). CONCLUSIONS: State alcohol policies may be effective in reducing, to a meaningful degree, aggression-related harms and vehicular hazards due to other drinkers, but mainly in those under 40.